DRUG UTILIZATION PATTERN OF ANTIDIABETIC DRUGS AMONG DIABETIC OUTPATIENTS IN A TERTIARY CARE HOSPITAL - Alex, Soumya Mary; Bs, Sreelekshmi; S, Smitha; Kn, Jiji; Menon, Arun S; P, Uma Devi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The aim was to evaluate the drug utilization pattern of anti-diabetic drugs in diabetic outpatients and monitor the adverse drug reactions (ADRs) associated with anti-diabetic therapy. Methods: A prospective observational study was carried out in adult diabetic patients visiting the outpatient Departments of General Medicine and Endocrinology of a tertiary care hospital. Demographic data, drug utilization pattern and ADRs due to anti-diabetic drugs were summarized. Results: In the present study, 99 (50.3%) of the 197 diabetic patients were males. Majority of patients were in the age group of 51-60 years (39.6%) and most of the patients (36.5%) had a diabetic history of <5 years. Metformin was the most commonly prescribed drug (68%), followed by sulfonylurea class of drugs (49.7%). Nearly, 42% patients were using insulin preparations with 30.4% using biphasic isophane human insulin. Majority of the patients (58.4%) were on multidrug therapy with two drug therapies being received by nearly 40%. Metformin was the most commonly prescribed drug in monotherapy (18.8%) and glimepiride + metformin was the most common two drug therapy (13.2%). Co-morbid condition was found in 172 patients (87.3%) with hypertension (68.5%) being the most common co-morbid condition. 17 ADRs were observed with hypoglycemia being the most common ADR reported. Conclusions: Metformin was the most commonly used drug. The prescribing trend also appears to be moving towards combination therapy particularly two drug therapies. Keywords: Drug utilization, Anti-diabetic drug, Adverse drug reaction.